Small clinical trials : issues and challenges / Charles H. Evans, Jr. and Suzanne T. Ildstad, editors ; Committee on Strategies for Small-Number-Participant Clinical Research Trials, Board on Health Sciences Policy, Institute of Medicine. (2025)
Summary goes here